2015
DOI: 10.1177/0954411915615469
|View full text |Cite
|
Sign up to set email alerts
|

Swelling and mechanical properties of physically crosslinked poly(vinyl alcohol) hydrogels

Abstract: Physically crosslinked poly(vinyl alcohol) gels are versatile biomaterials due to their excellent biocompatibility. In the past decades, physically crosslinked poly(vinyl alcohol) and poly(vinyl alcohol)-based hydrogels have been extensively studied for biomedical applications. However, these materials have not yet been implemented due to their mechanical strength. Physically crosslinked poly(vinyl alcohol) gels consist of a swollen amorphous network of poly(vinyl alcohol) physically crosslinked by microcrysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 98 publications
2
41
1
Order By: Relevance
“…However, beyond the 9 th freeze thaw cycle, the much enhanced crystallites tend to oppose the elastic response of the nanocomposite and the compressive strength decreases. In a study by Suzuki and Sasaki the Young's modulus of PVA cryogel was found to increase constantly with increasing number of freeze thaw cycles, however, no such observation was found in our case. Similar type of increase in mechanical properties of PVA hydrogel with increasing number of thermal cycles has also been reported by Millon and co‐workers .…”
Section: Resultscontrasting
confidence: 84%
“…However, beyond the 9 th freeze thaw cycle, the much enhanced crystallites tend to oppose the elastic response of the nanocomposite and the compressive strength decreases. In a study by Suzuki and Sasaki the Young's modulus of PVA cryogel was found to increase constantly with increasing number of freeze thaw cycles, however, no such observation was found in our case. Similar type of increase in mechanical properties of PVA hydrogel with increasing number of thermal cycles has also been reported by Millon and co‐workers .…”
Section: Resultscontrasting
confidence: 84%
“…The highest crystallinity, Young's modulus, and swelling degree were 36%, 1.46 GPa, and 470%, respectively . In recent decades, the physically crosslinked gels have attracted more attention, to avoid using chemical crosslinking agents and reagents …”
Section: Introductionmentioning
confidence: 99%
“…[ 80,81 ] In addition, crystallinity of a swollen gel is not always proportional to that of a dried gel. [ 82 ] As a result, any change in the crystallinity degree could not be appropriately assigned to the presence of starch, as it would be unclear what role a particular drying process may have played. X‐ray diffraction was then pursued to study the crystalline nature of the hydrogel samples in their as‐prepared state, as seen in Figure a.…”
Section: Introduction Of Synthetic Hydrogelsmentioning
confidence: 99%
“…The PVA‐based hydrogels consist of a swollen, amorphous network of PVA molecular chains that are physically crosslinked together with small, highly ordered pockets of PVA known as microcrystallites. [ 82 ] These microcrystallite regions develop from the freezing of water at very cold temperatures, giving way to small regions of minimal molecular motion that are highly concentrated with PVA. [ 87 ] With the PVA molecular chains in close proximity to one another, crystallite formation begins and it continues to progress during subsequent freezing cyles.…”
Section: Introduction Of Synthetic Hydrogelsmentioning
confidence: 99%